BLOOD-BASED PROGNOSTIC BIOMARKERS IN CROHN'S PATIENTS TREATED WITH BIOLOGICS: A NEW PROMISING TOOL TO PREDICT ENDOSCOPIC OUTCOMES. (21st January 2021) - Grova, Mauro; Crispino, Federica; Maida, Marcello; Renna, Sara; Mocciaro, Filippo; Casa, Angelo; Giulia, Rizzuto; Scimeca, Daniela; Di Mitri, Roberto; Macaluso, Fabio Salvatore; Orlando, Ambrogio
Abstract: Background and aims: There is a growing need for biomarkers of inflammation to monitor and predict therapeutic outcome in Crohn's disease (CD) patients. We aimed to evaluate whether the level of circulating blood cells, expressed as ratios (NLR, neutrophil-to-lymphocyte ratio; PLR, platelet-to-lymphocyte ratio; ELR, eosinophil-to-lymphocyte ratio and ENLR, eosinophil*neutrophil-to-lymphocyte ratio), could be used as early prognostic biomarker of endoscopic response (ER) in patients starting biological therapy with infliximab, adalimumab, vedolizumab and ustekinumab. Association with steroid-free clinical remission at week 54 and endoscopic disease activity at baseline, as well as other variables related with ER were also evaluated as secondary outcomes. Methods: Consecutive patients with CD who started biological therapy between June 2016 and July 2019 in two Italian tertiary centers were enrolled. We used multivariate analysis to evaluate whether NLR, PLR, ELR and ENLR at baseline and after 12 weeks of treatment could predict ER (SES-CD ≤ 2 or SES-CD ≤ 2 and Rutgeerts score i0-i1) after 54 weeks of treatment. Receiver operating characteristic (ROC) curves were generated to identify the area under the curve (AUC) and find the best cut-off values of NLR, PLR, ELR and ENLR for the prediction of ER. To enhance the diagnostic performance, these ratios were combined with baseline Harvey Bradshaw Index (HBI) in a prognostic model. Results: 107 patients were included. Patients who achieved ER had significantly lower baseline NLR (p = 0.025), ELR (p = 0.013) and ENLR (p = 0.021) compared with those without ER; similar results were confirmed after 12 weeks of treatment for ELR (p = 0.006) and ENLR (p = 0.026). AUC was 0.64 (p = 0.003), 0.67 (p = 0.006) and 0.65 (p=0.014) for NLR, ELR and ENLR, respectively. The best cut-offs values were included in the HBI-based prognostic model: 81.8% of patients with HBI ≥ 5 and higher ratios did not achieve ER, while all patients with HBI < 5 and lower ratios reached ER. Interestingly, ENLR was found to be linearly associated with SES-CD at baseline (p= 0.035). Conclusions: To the best of our knowledge, this is the first study assessing NLR, ELR and ENLR as predictive markers of therapeutic response in CD patients. Low levels of these ratios can predict endoscopic response and could be used in clinical practice for a better management of CD patients needing biological therapy. Further prospective studies are needed to confirm these results in larger cohorts.